A Perspective of International Collaboration Through Web-Based Telecommunication–Inspired by COVID-19 Crisis - Zaer, Hamed; Fan, Wei; Orlowski, Dariusz; Glud, Andreas N.; Andersen, Anne S. M.; Schneider, M. Bret; Adler, John R.; Stroh, Albrecht; Sørensen, Jens C. H. (Frontiers in Human Neuroscience, 2020)
The tsunami effect of the COVID-19 pandemic is affecting many aspects of scientific activities. Multidisciplinary experimental studies with international collaborators are hindered by the closing of the national borders, logistic issues due to lockdown, quarantine restrictions, and social distancing requirements. The full impact of this crisis on science is not clear yet, but the above-mentioned issues have most certainly restrained academic research activities. Sharing innovative solutions between researchers is in high demand in this situation. The aim of this paper is to share our successful practice of using web-based communication and remote control software for real-time long-distance control of brain stimulation. This solution may guide and encourage researchers to cope with restrictions and has the potential to help expanding international collaborations by lowering travel time and costs.